Infant motor development - Piek, Jan P. (Human Kinetics, 2006)
Infant Motor Development is the first text to concentrate on motor development during infancy--the stage in which the greatest qualitative changes in the life span occur. It is an excellent introduction to the most relevant and common issues researchers, clinicians, and parents face. This groundbreaking text combines theory with application to provide the most current account of infant motor ability and disability--including the latest prenatal research--all in one comprehensive resource. Infant Motor Development presents criteria for selecting the most appropriate assessment tool and intervention strategies to improve the motor functioning of infants with particular problems. The result is an essential textbook for graduate students and an up-to-the-minute reference for health professionals and researchers. Infant Motor Development is organized into four parts covering theory, research, assessment, and intervention. It integrates information from a variety of disciplines to encourage a broad understanding of infant motor development. Topics include the development of voluntary movements such as posture, stability, balance, and orientation; manual control of reaching and grasping; locomotor control of creeping and walking; the unique difficulties faced by premature infants; and an examination of two disabilities with devastating consequences to motor control: cerebral palsy and Down syndrome. Infant Motor Development contains many helpful features: Sidebars highlighting the relationship between research and therapeutic practice; Chapter objectives and summaries that clarify the main ideas and simplify the review process; Key points that highlight important concepts throughout the text; Glossary of terms that clearly defines the concepts used in infant motor development. With Infant Motor Development, students will understand the subject area from a variety of disciplines and perspectives, researchers will discover the most current theory and findings, and clinicians will learn to apply theory and research in their work with infants